How do students solve reversible thinking problems in mathematics? - Aneu Pebrianti; Sufyani Prabawanto; Elah Nurlaelah (Universitas Hamzanwadi, 2023)
Reversible thinking is a cognitive activity in finding a solution to a problem by arranging the direction of logical thinking from the end to the starting point. Reversible thinking requires a student to think logically in two ways. Therefore, reversible thinking influences students' success in solving problems. This study aims to identify students' thinking processes in solving problems that require reversible thinking ability. This research was conducted on junior high school students in Bandung, West Java, Indonesia, using test instruments, interviews, and documentation studies. The tests given consisted of two types of problems, including tests on forward-thinking problems and tests on reversible thinking problems. The research subjects were students with high average mathematics scores in their class. The study found that students could answer the tests on forward-thinking problem-solving very well but could not work on similar questions with the backward-thinking process. Based on the interview results, one of the causes for the need for more backward-thinking ability is the limited learning resources or context when students first learn the concept.